2004
DOI: 10.1046/j.0022-202x.2004.22231.x
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib Mesylate Inhibits Platelet-Derived Growth Factor Receptor Phosphorylation of Melanoma Cells But Does Not Affect Tumorigenicity In Vivo

Abstract: Platelet-derived growth factor (PDGF) and its cognate receptor are widely expressed on melanomas. Coexpression of the growth factor and receptor suggests their role in autocrine or paracrine growth mechanisms. Imatinib mesylate was previously reported to have specific activity in inhibiting select tyrosine kinase receptors, including PDGF and c-Kit. Melanoma cells express abundant levels of the PDGF receptor (PDGFR). Nevertheless, c-Kit expression is progressively lost as the cells take on a more highly metast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
41
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 22 publications
4
41
0
1
Order By: Relevance
“…No correlation between the receptor expression profile and the in vitro growth inhibition by imatinib could be detected. These results are in line with recently published data about melanoma-bearing athymic nude mice treated with imatinib without efficacy, regardless of whether the melanoma cells expressed PDGF-R or c-kit (McGary et al, 2004).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…No correlation between the receptor expression profile and the in vitro growth inhibition by imatinib could be detected. These results are in line with recently published data about melanoma-bearing athymic nude mice treated with imatinib without efficacy, regardless of whether the melanoma cells expressed PDGF-R or c-kit (McGary et al, 2004).…”
Section: Discussionsupporting
confidence: 82%
“…Thus, by inhibiting cell viability and proliferation via inhibition of receptor tyrosine kinases, imatinib might be a successful therapeutic in malignant melanoma. A first study investigating the growth behaviour of two human melanoma cell lines in athymic nude mice showed that imatinib treatment of these mice resulted in an inhibition of PDGF-R phosphorylation but no decrease in tumour size (McGary et al, 2004). In contrast, a recent report on murine B16F10 melanoma cells injected into C57B16 mice revealed a strong and efficient tumour growth inhibition by imatinib (Redondo et al, 2004).…”
mentioning
confidence: 94%
“…Pericytes express PDGFRB, and in normal angiogenesis, the recruitment of pericytes will stabilize neovessels [53]. MC are known to be able to express this same receptor [54], and in the present study, PDGFRB was specifically expressed by angiotropic MC in several human samples. Cancer stem cells are more resistant to therapy, and interestingly resistance to (V600E) B-RAF kinase inhibitor has been shown to be caused in part by MC upregulating PDGFRB [55].…”
Section: Discussionmentioning
confidence: 59%
“…In a murine B16F10 melanoma model, imatinib mesylate resulted in tumor growth inhibition (25). Furthermore, imatinib mesylate treatment of human melanoma xenografts in athymic nude mice has been shown to inhibit platelet-derived growth factor receptor phosphorylation albeit without reducing tumor size (26). Because imatinib mesylate targets both KIT and platelet-derived growth factor receptor activities, the relative roles of these two receptor tyrosine kinases in these models have yet to be determined.…”
Section: Discussionmentioning
confidence: 99%